Human resource management / Scott Snell, George Bohlander - Scott Snell (Thomson, 2007)
1.Human resources management in perspective - 2. Meeting human resources requirement - 3. Developing efectiveness in human resource - 4. Implementing compensation and security - 5. Expanding human resource managegement horizons